Supplementing Artificial Diets for Catfish (Glarias macrocephalus)Fry with Tubifex - Hashim, Roshada; Ali, Ahyaudin; Mat Saat, Noor Azam (Universiti Putra Malaysia Press, 1993)
Three-week-old catfish (Clarias macrocephalus) fry were fed experimental diets at protein levels of 30% and 35% fish meal dominant and 35% and 40% soybean dominant types for 8 weeks. Nine treatments were tested with four treatment consisting wholly of experimental diets, one ofTubifex (control) and the remaining four diets supplemented with live Tubifex. Fish reared on experimental diets supplemented with live Tubifex fed more actively and showed better growth and feed efficiency than those reared without supplemented diets. Those on the 30% and 35% fish meal dominant feed showed significantly better growth and feed conversion than those fed 35% 40% soybean dominant diet.